2017
DOI: 10.1016/j.ajo.2017.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Rectus Transposition: A Novel Procedure for Abducens Palsy

Abstract: Purpose Superior rectus transposition (SRT) has been popularized for the treatment of abduction deficiencies. Potential complications include induced vertical deviation and torsion. A new procedure, the inferior rectus transposition (IRT) may be similarly beneficial for patients at risk for post-operative vertical deviation or incyclotropia. The purpose of this study is to describe the outcomes of patients undergoing IRT. Design Prospective, interventional case series Methods Five patients in an academic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Inferior rectus transposition (IRT) was first described by Velez et al , who stated that IRT may address both the esotropia and hypertropia by intervening a single vertical rectus muscle in patients with lateral rectus palsy with a preexisting hypertropia. [24] None of the single VRT patients have shown postoperative symptomatic cyclotorsional diplopia or significant vertical tropias. A single nonrandomized study comparing patients undergoing single VRT with simultaneous MRc against those undergoing double VRT is included in the review and is discussed separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inferior rectus transposition (IRT) was first described by Velez et al , who stated that IRT may address both the esotropia and hypertropia by intervening a single vertical rectus muscle in patients with lateral rectus palsy with a preexisting hypertropia. [24] None of the single VRT patients have shown postoperative symptomatic cyclotorsional diplopia or significant vertical tropias. A single nonrandomized study comparing patients undergoing single VRT with simultaneous MRc against those undergoing double VRT is included in the review and is discussed separately.…”
Section: Discussionmentioning
confidence: 99%
“…[712] Moreover, torticollis correction has been reported in two studies, and Velez et al have reported a correction of 27° of torticollis. [224]…”
Section: Discussionmentioning
confidence: 99%
“…When combined with an augmentation suture, either with or without simultaneous adjustable medial rectus recession, IRT was shown to significantly improve the esotropia, abduction, and head turn in a small group of patients who were deemed at risk of hypothetical exacerbation by SRT due to preoperative hypertropia or intorsion of the operative eye. 43 IRT can also achieve a small downward shift in the operative eye that can help correct a preexisting hypertropia. The initial report was in the context of abducens nerve palsy, so a role for primary IRT in DS is yet to be defined.…”
Section: Inferior Rectus Transpositionmentioning
confidence: 99%
“…To date, there have been many articles mentioning the efficacy of several new transposition techniques, such as superior rectus transposition with or without medial rectus recession and inferior rectus transposition with medial rectus recession 1418. A recent study by Lee and Lambert19 found a comparable surgical outcome of full tendon VRT with or without Foster suture and superior rectus transposition with medial rectus recession.…”
Section: Discussionmentioning
confidence: 99%